Mental health research priorities for Europe. (November 2015) - Wykes, Til; Haro, Josep Maria; Belli, Stefano R; Obradors-Tarragó, Carla; Arango, Celso; Ayuso-Mateos, José Luis; Bitter, István; Brunn, Matthias; Chevreul, Karine; Demotes-Mainard, Jacques; Elfeddali, Iman; Evans-Lacko, Sara; et al.
Summary: Mental and brain disorders represent the greatest health burden to Europe—not only for directly affected individuals, but also for their caregivers and the wider society. They incur substantial economic costs through direct (and indirect) health-care and welfare spending, and via productivity losses, all of which substantially affect European development. Funding for research to mitigate these effects lags far behind the cost of mental and brain disorders to society. Here, we describe a comprehensive, coordinated mental health research agenda for Europe and worldwide. This agenda was based on systematic reviews of published work and consensus decision making by multidisciplinary scientific experts and affected stakeholders (more than 1000 in total): individuals with mental health problems and their families, health-care workers, policy makers, and funders. We generated six priorities that will, over the next 5–10 years, help to close the biggest gaps in mental health research in Europe, and in turn overcome the substantial challenges caused by mental disorders.